The Role of Islamic Economics on Regional Economic Development: A Case in Indonesia - Antonio, Muhammad Syafii (Management and Sustainability, 2023)
The monetary crisis that shock Indonesia past years ago has alerted many parties to the importance of strong economic fundamentals and empowerment of the people's economy. A monetary sector that is not supported by a strong real sector is suspected of harboring a time bomb waiting for a moment to collapse the achievements of national economic development. The monetary crisis also made us realize the importance of empowering the people's economy. A development paradigm that does not leave economic growth entirely to the role of large entrepreneurs, but to all parties, especially micro, small and medium enterprises (MSMEs). This study tries to see the important role of Islamic economics in regional economic development.